Design of optically pumped cesium beam tube with hexapole magnetic system for longer lifetime and better SNR - Chen, Haijun; Yan, Yufei; Chen, Jingbiao; Feng, Jinjun (Frontiers in Physics, 2022)
In order to get a better tradeoff between the long lifetime and high performances of cesium beam atomic clocks, we proposed a design scheme of compact optically pumped cesium beam tube (OPCBT) based on hexapole magnetic focusing (HMF) system for the confinement of cesium. A practical optically pumped cesium beam tube without HMF system has been implemented and tested with high-stability laser by modulation transfer spectroscopy (MTS), and a signal-to-noise ratio (SNR) of 18000 in 1Hz bandwidth and Allen variance of 2×10^(-12)/√τ were obtained. Based on this test, the simulation analysis results of the newly designed tube with HMF show that the predicted lifetime can reach over 20 years without degradation of the performances, and the expected frequency stability of the clock can be 6.5×10^(-13)/√τ with a lifetime of 10 years.